2015
DOI: 10.1063/1.4919328
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic properties of CuFe1−xCrxO2 nanoparticles surrounded by amorphous SiO2

Abstract: CuFe1−xCrxO2 (0 ≤ x ≤ 1.0) nanoparticles surrounded by amorphous SiO2 with an average diameter of 30–50 nm were synthesized using a wet chemical method. The annealing temperatures were controlled to yield various sizes of single-phase CuFe1−xCrxO2 nanoparticles. CuFeO2 bulk crystal is known to have a multiferroic delafossite structure with two Néel temperatures of 11 and 14 K; however, the transition temperature shifted higher as the Cr–ion doping level increased. In addition, the lattice constants decreased i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…The CuFeO 2 bulk crystal is known to be a multiferroic material with two Neel temperatures of 11 and 14 K [83][84][85][86][87][88][89][90]. However, doping with Cr caused the transition temperature shifted higher as the Cr-ion doping level increased [91]. They also observed weak ferromagnetic behaviour with no coercivity and changes in the lattice constants due to increased Cr-ion doping.…”
Section: Magnetic Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The CuFeO 2 bulk crystal is known to be a multiferroic material with two Neel temperatures of 11 and 14 K [83][84][85][86][87][88][89][90]. However, doping with Cr caused the transition temperature shifted higher as the Cr-ion doping level increased [91]. They also observed weak ferromagnetic behaviour with no coercivity and changes in the lattice constants due to increased Cr-ion doping.…”
Section: Magnetic Propertiesmentioning
confidence: 99%
“…Doping can also change the magnetic or photo-properties of the pristine materials. The doping could cause changes of the magnetic properties [91], optical properties [99], andimproved their oxygen storage capacity (OSC) [100].…”
Section: Dopingmentioning
confidence: 99%
“…reported that the electronic, thermoelectric and optical properties are significantly influenced by inducing spin entropy and lattice strain occurring due to the introduction of Cr 3+ ions. In the same year, Mori K [28]. proposed that the magnetic transition temperature increases and the magnetization enlarges as the Cr 3+ contents increase.…”
Section: Introductionmentioning
confidence: 99%